Evaluation of the viability of sedes of sacha inchi Plukenetia volubilis L. preserved at 4° C - Carrillo, Fredesvinda (2021)
Sacha inchi Plukenetia voluvilis L., is a species native to and promising cultivation in the Peruvian Amazon, which has nutritional properties (omega 3) beneficial for the human body., therefore the interés of studying and evaluating the shelf life under partular conditions. The aim of this study was to evaluate the viability of sacha inchi seeds, stored in a cold chamber, with moisture contents between 4.0 and 6.8%, for eigth years. 27 accessions of Sacha inchi were used, the seed of which were partially and completely scarified, and were soaked in distilled water for 12 hours, then disinfected with 3% captan (fungicide). The scarified seeds of a total of 27 accesiion were sown on towel paper moistened with distilled water and placed in the germinator under controlled light and temperature conditions, while theseed of the partially scarified accessions were sown on fattening trays containing a misxture of sand, moss and coconut fibre, a placed in a tinglage to the environment. The results show that the germination process on scarfied seeds located in the germinator begins after 12 days plant and 20 days in partially scarified seeds placed in the tingled. The viability of the seeds after 8 years of cold storage was 80 -100% in 44% of the material evaluated. In addition, sacha inchi was found to have orthodox behaviour and can be kept with moisture content of the seed between 4, 0 to 7.5 %.